Penerapan Prinsip Persona Non Grata Terhadap Duta Besar Ditinjau Dari Perspektif Hukum Internasional (Studi Kasus Penganiayaan TKI Oleh Duta Besar Arab Saudi Di Jerman) - Devi Yusvitasari (Jurnal Locus Delicti, 2020)
A country needs to make contact with each other based on the national interests of each country related to each other, including among others economic, social, cultural, legal, political, and so on. With constant and continuous association between the nations of the world, it is one of the conditions for the existence of the international community. One form of cooperation between countries in the world is in the form of international relations by placing diplomatic representation in various countries. These representatives have diplomatic immunity and diplomatic immunity privileges that are in accordance with the jurisdiction of the recipient country and civil and criminal immunity for witnesses. The writing of the article entitled "The Application of the Principle of Non-Grata Persona to the Ambassador Judging from the Perspective of International Law" describes how the law on the abuse of diplomatic immunity, how a country's actions against abuse of diplomatic immunity and how to analyze a case of abuse of diplomatic immunity. To answer the problem used normative juridical methods through the use of secondary data, such as books, laws, and research results related to this research topic. Based on the results of the study explained that cases of violations of diplomatic relations related to the personal immunity of diplomatic officials such as cases such as cases of persecution by the Ambassador of Saudi Arabia to Indonesian Workers in Germany are of serious concern. The existence of diplomatic immunity is considered as protection so that perpetrators are not punished. Actions against the abuse of recipient countries of diplomatic immunity may expel or non- grata persona to diplomatic officials, which is stipulated in the Vienna Convention in 1961, because of the right of immunity attached to each diplomatic representative.